Answer:
a) Profit 1 = (P 1 - 3)*6 = 54
Profit 2 = (P 2 -6)*3 = 9
b) Profit 1 = (P 1 - 3)*6 = 36
Profit 2 = (P 2 -6)*3 = 9
Step-by-step explanation:
a)
Cournot equilibrium :
for firm 1 :
P 1 = 18 - X - Y
R 1 = (18-Y)X - X^2
MR 1 = (18-Y) - 2 X = MC = 3
X= (15-Y)/2 .........(1)
for firm 2 :
P 2 = 18 - X - Y
R 2 = (18-X)Y - Y^2
MR 2 = (18-X) -2 Y = MC = 6
Y= (12-X)/2 ...........(2)
using this value of Y in equation (1),
X = (15 -(12-X)/2)/2
X = (18+X)/4
3 X / 4 = 18 / 4
X = 6
Y = 3
P 1 = P 2 = 9
Profit 1 = (P 1 - 3)*6 = 54 (ANSWER)
Profit 2 = (P 2 -6)*3 = 9 ((ANSWER)
b)
for firm 1
X = 18-Y -P 1
R 1 = (18-Y)P 1 - P 1^2
MR 1 = (18-Y) - 2P 1 = 3
P 1 = (15-Y)/2
X = (18-Y - (15-Y)/2) = (21-Y)/2 ..........(3)
for firm 2,
Y = 18-X - P 2
R 2 = (18-X)P 2 -P 2^2
MR 2 =(18-X) -2P 2 = 6
P 2 = (12-X)/2
Y = (18-X - (12-X)/2) = (24 - X)/2
Using it in (3)
X = (21 - (24-X)/2))/2 = (18 +X)/4
X = 6, Y = 3 , P 1 = P 2 = 9
Profit 1 = (P 1 - 3)*6 = 36 (ANSWER)
Profit 2 = (P 2 -6)*3 = 9 ((ANSWER)